Cost‐effectiveness of early detection of atrial fibrillation via remote control of implanted devices. Issue 5 (25th April 2014) - Lorenzoni, Giulia; Folino, Franco; Soriani, Nicola; Iliceto, Sabino; Gregori, Dario
Abstract Rationale, aims and objectives Atrial fibrillation (AF) is an independent risk factor for stroke, and its incidence is high in patients implanted with pacemakers (PMs) and implantable cardioverter defibrillators (ICDs). The aim of our study is to evaluate the potential benefit of remote control (RC) on the incidence of stroke related to AF in patients with new‐onset AF implanted with PMs and ICDs and to evaluate the impact of RC on the consumption of medical resources. Method The study consisted of two cohorts of patients: group AMB (patients attending ambulatory care clinics from August to October 2013) and group RC (patients followed remotely). All detected cases of new‐onset AF were confirmed by the electrogram stored in the device's memory or by standard electrocardiogram recording. Monte Carlo simulations were performed in order to evaluate the potential risk reduction of stroke related to AF. The costs were estimated from the perspectives of the hospital, the patients and the National Health Service. Result We enrolled 223 patients in group RC and 359 in group AMB. We detected 20 new‐onset cases of AF, and the median time to AF detection was 2 days in the RC and 78 days in the ambulatory care clinic control. Management of patients was more efficient with RC, with an average savings in direct costs of €40.88 per year per patient. Through the use of Monte Carlo simulations, we showed that the early detection of new‐onset AF may provide a relative risk reduction of 94.3% for stroke in PM‐implanted patients older than 55 years. Conclusion RC potentially provides a risk reduction for stroke because it allows an early detection of new‐onset AF. Moreover, it is also a cost‐saving means of follow‐up.